The impact of transhumance abandonment on land use changes in Mount Pindos (Greece) - Takola E.; Sidiropoulou A.; Karatassiou M. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Τranshumance was one of the main income sources for the inhabitants of Avdella village in Mount Pindos, until a few decades ago. This land use management created a mosaic of different ecological habitats. However, due to urbanization and technology evolution, transhumance was reduced, leading to significant changes for the mountainous grasslands. The purpose of this paper was to determine the changes in vegetation during the period 1983-2003, using landscape metrics. Μetrics were calculated with Patch Analyst (ArcGIS) in order to assess human impact on biodiversity and landscape characteristics. The analysis showed that changes in land cover during 1983-2003 were the result of transhumance decline and the abandonment of intensive human activities. Landscape metrics indicated expansion of forests and shrublands and reduction of grasslands due to the reduction of grazing animals. Τhe landscape in Avdella tends to become more fragmented and land use patch distribution more uneven. Landscape metrics imprinted in detail the change of the landscape during the period of investigation.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)